(untitled) (Journal of Education, Humanities, and Social Research, 2025)
Although substantial research supports language aptitude’s critical role in second language acquisition (SLA), how individual differences in aptitude interact with instructional approaches to influence grammar learning outcomes remains underexplored. Most prior studies examined aptitude effects in isolated instructional contexts, leaving the potential causal mechanisms of aptitude across instructional treatments largely uninvestigated. This systematic review analyzed nine empirical studies to characterize the relationship between language aptitude and L2 grammar acquisition, and determine whether instructional variations moderate this association. Findings demonstrated a robust correlation between aptitude and grammar learning success, but revealed differential outcomes depending on instructional design. Methodological inconsistencies in measuring aptitude and grammar proficiency, alongside mediating contextual factors, were identified as potential confounders. The review emphasizes integrating aptitude assessments into instructional design for grammar pedagogy and advocates for standardized measurement tools to advance SLA research. Directions for future inquiry include longitudinal investigations of aptitude-instruction interactions and expanded theoretical frameworks.